Social ecological resources for youths living with HIV in western Uganda - Vindevogel, Sofie; Kimera, Emmanuel (Frontiers in Psychology, 2023)
The adversities faced by youths living with HIV (YLWH) are manifold, resulting not only from the health impact but also from society’s response to HIV and the people living with it. This study sought to explore these youths’ perceptions and representations of what promotes resilience. Photovoice methodology was chosen to elicit first-person accounts that are grounded in lived experience and experiential knowledge. Eleven young people, boys and girls aged 14-21 living in western Uganda, participated in seven group sessions aimed at imagining, producing and discussing visual stories about what fosters resilience in the face of HIV-related adversity. The visual stories were subjected to inductive content analysis by the participants, and then thematically analyzed and interpreted by the researchers using the theoretical framework of social-ecological resilience. This showed that participants experience well-being amidst HIV-related adversity through managing tensions in material resources, sense of identity, power and control in their lives, cultural adherence, relationships, sense of cohesion and social justice. The findings add to the body of knowledge on youth resilience in Sub-Saharan Africa by documenting multisystemic resources for YLWH in Ugandan communities. The findings further show that resources are highly incidental and situational, neither widely available nor structurally embedded in society. The study therefore informs the global HIV/AIDS agenda to spur ecologies of resilience around YLWH.